Evaluation of Association Studies and Meta-Analyses of eNOS Polymorphisms in Type 2 Diabetes Mellitus Risk - Wang, Di; Liu, Liangshu; Zhang, Chengyu; Lu, Wensheng; Wu, Feifei; He, Xiaofeng (Frontiers in Genetics, 2022)
Numerous studies reported the associations between endothelial nitric oxide synthase (eNOS) polymorphisms (4b/a VNTR (rs869109213), G894T (rs1799983) and T786C (rs2070744)) and type 2 diabetes mellitus (T2DM) risk. However, the conclusions were incongruent. Moreover, since no published meta-analyses were performed, a key issue regarding false-positive results needs to be addressed. Furthermore, four new articles have been published on these issues. Therefore, an updated meta-analysis was conducted to further explore these associations. Studies were searched by using the PubMed, China National Knowledge Infrastructure (CNKI) , Medline, Embase, ISI(International Statistical Institute) and the China Wanfang databases. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate the associations using five genetic models. Furthermore, the false-positive report probability (FPRP), Bayesian false discovery probability (BFDP), and the Venice criteria were employed to assess the credibility of statistically significant associations. Overall, the eNOS 4b/a polymorphism was associated with a significantly decreased T2DM risk in Asians (bb vs aa: OR=0.44, 95% CI=0.23–0.84; ab + bb vs aa: OR=0.45, 95% CI=24–0.86; bb vs aa +ab: OR=0.73, 95% CI=0.59–0.91; b vs a: OR=71, 95% CI=0.57–0.88); the eNOS G894T polymorphism was associated with a significantly increased T2DM risk in Asians (GT vs GG: OR=1.52, 95% CI=1.15–2.01; GT + TT vs GG: OR=1.52, 95% CI=1.15–2.01; T vs G: OR=1.39, 95% CI=1.09–1.76); the eNOS T786C polymorphism was associated with a significantly increased T2DM risk in Indian (TC vs TT: OR = 1.93, 95% CI = 1.27–2.94; TC + CC vs. TT: OR = 2.06, 95%CI = 1.26–3.36; C vs. T: OR = 1.90, 95%CI = 1.17–3.08). However, when a sensitivity analysis was performed after excluding low quality and Hardy–Weinberg Disequilibrium (HWD) studies, no significant association was found for the the eNOS G894T polymorphism. After credibility assessment, we identified “less-credible positive results” for the statistically significant associations in the current meta-analysis. In conclusion, this article suggests that all substantial relationships between eNOS 4b/a, G894T, and T786C polymorphisms and T2DM risk are most likely due to false positive results rather than real connections or biological variables.